The Effectiveness of Interactive Video Learning Media to Improve Understanding of Cllas V Elementary School Students - Yasnimar, Mita; Alpusari, Mahmud (Education Generation Journal, 2023)
This study aims to ascertain how effective interactive video learning media is in increasing the understanding of fifth grade elementary school students. In this study using the type of research Quasy experimental group design. In this study the samples taken were divided into two groups, namely the experimental group and the control group. Data analysis techniques included descriptive tests, hypothesis testing using the Independent sample T-test and N-Gain test techniques. Based on the results of the research pretest, it was found that the average student learning outcomes of the experimental class were 60.1 and the pretest results of the experimental class received average results. – average 63.2. The two classes were given different treatment, in the experimental class learning took place using interactive video media, while in the control class using conventional media (images). However, when students took the research posttest after being given the different treatment earlier, the average student learning outcomes increased by 87.7 and the control class received an average result of 80.5. The pretest and posttest values ​​of students in the experimental and control classes were then analyzed using the N-Gain test where based on the N-Gain test analysis it was found that the experimental class got an average N-Gain interpretation value of 67.83 and in the control class scored 47.84. Based on these tests, it was found that interactive video media was effective in increasing student understanding, while conventional media was less effective in increasing student understanding. In the independent sample T-test, a sig value of 0 was obtained. 003 based on these results it can be stated that 0.003 <0.005 then H1 is accepted. It can be concluded that interactive video learning media has a positive influence in increasing the understanding of fifth grade elementary school students